MODEL PEMBELAJARAN STEAM MENGGUNAKAN GOOGLE CLASSROOM TERHADAP KEMAMPUAN BERPIKIR KRITIS MAHASISWA DI PROGRAM STUDI PENDIDIKAN BIOLOGI - Oktafiany, Hesty; Irwandi, Irwandi; Sakroni, Sakroni (Universitas Negeri Malang, 2022)
Along with the development of 21st century technology, we are required to face the industrial revolution 4.0 in which the implementation of learning is expected to be more innovative, critical and creative. With progress in this level of education, superior and good quality human resources can be created in terms of religion, attitudes, and knowledge. The aim of this research is to determine the effect of the STEAM (Science, Technology, Engineering, Art and Mathematics) learning model by using Google Classroom (GC) on students' critical thinking skills at the Biology Education Study Program in the Muhammadiyah University of Bengkulu. This study was pre-experimental research using a one-group pretest & post-test design. The population was fourth-semester students of the Biology Education Study Program at the Muhammadiyah University of Bengkulu especially for the Plant Physiology Course. This study only used one class with a similar sample which consisted of 29 students in the pretest and post-test groups. The data collection used the test to measure students' critical thinking skills involved use essay test. Data were analyzed using the t-test paired samples test (in pairs). Based on the result there was a significant influence from the application of the STEAM (Science, Technology, Engineering, Art and Mathematics) learning model by using Google Classroom (GC) on students’ critical thinking skills at the Biology Education Study Program in the Muhammadiyah University of Bengkulu